The effects of inflammatory response associated with traumatic spinal cord injury in cutaneous wound healing and on expression of transforming growth factor-beta1 (TGF-beta(1)) and platelet-derived growth factor (PDGF)-A at the wound site in rats - AKAKIN, DİLEK; ÇETİNEL, ŞULE (INFORMA HEALTHCARE, 2008)
At the cellular level, spinal cord injury (SCI) provokes an inflammatory response that generates substantial secondary damage within the cord, but also may contribute to its repair. The aim of this study was to investigate the effects of inflammatory response associated with SCI in cutaneous wound healing and on expression of transforming growth factor-beta1 (TGF-beta(1)) and platelet-derived growth factor (PDGF)-A at the wound site in rats. At the 14th day analysis, the mean TGF-beta(1) score in trauma group (I) was significantly lower than that in control group (C) (2.60 +/- 0.90 vs. 3.64 +/- 0.37, respectively; p < 0.05). The mean score for PDGF-A expression in group I was similar to the corresponding value in group C (2.42 +/- 0.74 vs. 2.94 +/- 0.72, respectively). Compared to group C, group I had significantly lower mean scores for epidermal and dermal regeneration, but higher mean scores for granulation tissue thickness and similar scores for angiogenesis. The dermal layer contains diffuse deposition of collagen fibers that are not organised as in control rat skin, and intraepidermal and subepidermal vasocongestion is distinct. Based on the results on the parameters evaluated in the study, experimental SCI in rats results in delay in wound healing and low intensity of TGF-beta(1) in the dorsal wound-tissue specimens.
Keywords: platelet derived growth factor; spinal cord injury; transforming growth factor; wound healing; REPAIR; IMPACT